Development and performance evaluation of a kerosene chicken incubator - Ndirika, V.I.O.; Ademoye, S.A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2007)
A kerosene-heated chicken egg incubator of 160 eggs capacity was developed and its performance evaluated based on incubation temperatures, relative humidity, period of incubation and percentage of eggs hatched. The results revealed that the average incubation temperature and relative humidity obtained were 38.68 0C and 58.16% respectively at average ambient conditions of 27.20C temperature and 84.68% relative humidity. Also, the incubation temperature and incubation relative humidity at different levels of tray varied between 36.8-40.90C and 46.5 – 67% respectively, but the differences in their mean values at different egg tray levels were not statistically significant at 5% level. Up to 80% of the eggs were hatched over a period of 22 days at hatching temperature of 37.50C within ambient conditions of 270C temperature and 68.5% relative humidity. The results obtained were found to conform with the results obtained from already established research works on natural incubation method for chicken.